(untitled) (Research, Society and Development, 2021)
The need to apply cleaner technologies for effluent and water treatment is the key to minimize the impacts caused to the environment and recovery of water resources. Among these technologies the membrane technology stands out because it has advantages such as energy savings, easy operation, replacing conventional processes, recovering products with high added value, flexibility in the design of systems and in the development of hybrid processes. This paper aims to perform a review of the process of separation by membranes, method of obtaining and recent studies that use zinc oxide (ZnO) as an inorganic load to obtain nanocomposite membranes. Hybrid membranes have been conquering space in the scientific environment because they present improvements in physical, mechanical and chemical properties. From the studies performed by researchers, it was found that ZnO has been incorporated as a load to obtain polymeric nanocomposite membranes, because it presents improvements in their hydrophilicity, water flow, reduced fouling and chlorine resistance characteristics of the membranes obtained, thus presenting potential to be applied in wastewater treatment.